2020
DOI: 10.7441/joc.2020.02.07
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of a Firm’s CSR Initiatives on Brand Loyalty and Brand Image

Abstract: The objective of this study is to examine the impact of corporate social responsibility (CSR) initiatives of a firm as one of the critical factors to improve the competitiveness of the firm in today's aggressive market environment. The influence of corporate social responsibility on brand loyalty and brand image, which distinguishes the firm from other competitors, was evaluated in the study. Data from 364 consumers were collected through adapted and structured questionnaires for the period from August 2018 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 42 publications
(49 reference statements)
3
32
0
1
Order By: Relevance
“…Companies are aware of the benefits of the CSR idea. It is proven that the implementation of CSR has a positive effect on product perception, brand loyalty, and image of the company, and CSR can be used as an effective tool how to differentiate products from the other competitors and increase the competitive advantage of the company (Lu et al, 2020;Bardos et al, 2020). Despite these competitive benefits of CSR implementation, according to Boccia et al (2019), price still remains the key criterion in most of the customers' decision-making.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Companies are aware of the benefits of the CSR idea. It is proven that the implementation of CSR has a positive effect on product perception, brand loyalty, and image of the company, and CSR can be used as an effective tool how to differentiate products from the other competitors and increase the competitive advantage of the company (Lu et al, 2020;Bardos et al, 2020). Despite these competitive benefits of CSR implementation, according to Boccia et al (2019), price still remains the key criterion in most of the customers' decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these competitive benefits of CSR implementation, according to Boccia et al (2019), price still remains the key criterion in most of the customers' decision-making. The implementation of CSR has a positive effect on the attitudes and behaviour of employees (Wang et al, 2020), identification of the employee with the company, his perception of involvement in meaningful activities, and motivation to work more (Breger et al, 2020) or lower employee's turnover (Vveinhardt & Sroka, 2020) while we must not forget, that even in the age of automation, the human factor remains still irreplaceable (Lazanyi et al, 2020). From the managerial point of view, it is of particular interest to investigate the influence of CSR on sustainability or continuance of the activity (Dayanandan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CSR, whether legal or ethical or philanthropic, as perceived by customers, enhances positive functional and symbolic images in the minds and hearts of customers (He and Lai, 2014). In the discussion of the relationship between CSR effect on brand loyalty, several authors have reported that CSR improves brand loyalty and performance (Jeon et al, 2020;He and Lai, 2014;Lu et al, 2020;Prieto et al, 2020), even though others studies such as Wang et al (2015) have reported that CSR does not influence brand loyalty. Nevertheless, the majority of evidence supports the existence of that causal relationship.…”
Section: Brand Loyaltymentioning
confidence: 99%
“…Differences could be caused by various factors, including the company's age and size (Çera et al, 2020). According to Lu et al (2020), CSR implementation positively affects product perception, brand loyalty, and image, which increases the competitive advantage of the enterprise. Social networks have a significant impact on communication strategy development for SMEs.…”
mentioning
confidence: 99%